2013
DOI: 10.1055/s-0032-1333289
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement von Krankenhausärzten: Welche Rolle spielen Sozialkapital und Persönlichkeitseigenschaften?

Abstract: Work engagement has been proven to be a viable indicator of physical and mental well-being at work. Research findings have shown a link between work engagement and both individual and organizational resources. The aim of the present study is to test the hypothesized relationships between personal traits (Big-5), the quality of the social work environment (social capital) and work engagement among hospital (n=35) physicians (n=387) in North-Rhine-Westphalia, Germany. Structural equation modeling (SEM), combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found that higher levels of social capital in the workplace are associated with lower levels of emotional exhaustion 12 ) and depression 13 , 14 ) and higher levels of psychological wellbeing 15 ) . Other studies have found that higher levels of social capital are associated with higher levels of job satisfaction 16 ) , work engagement 11 , 15 , 17 , 18 , 19 , 20 ) and self-reported job performance 15 ) . Thus, social capital is associated with important work-related outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have found that higher levels of social capital in the workplace are associated with lower levels of emotional exhaustion 12 ) and depression 13 , 14 ) and higher levels of psychological wellbeing 15 ) . Other studies have found that higher levels of social capital are associated with higher levels of job satisfaction 16 ) , work engagement 11 , 15 , 17 , 18 , 19 , 20 ) and self-reported job performance 15 ) . Thus, social capital is associated with important work-related outcomes.…”
Section: Introductionmentioning
confidence: 96%